Privatising the Third World - J.R. SHACKLETON (PSL Quarterly Review, 2013)
A remarkable feature of recent economic policy in many Third World countries has been the adoption of privatisation and deregulation by previously “statist” governments. Perhaps more fundamentally, this process is being accompanied by measures to liberalise markets and encourage competition, going against the ideal of centralised planning that has been so powerful on development thinking. The work examines these trends and the seemingly genuine changes of attitudes towards the state’s role in the economy in many Third World countries.